Importance of Therapeutic Drug Monitoring to Detect Drug Interaction between Pazopanib and Warfarin: A Case Report - Shinya Takasaki; Hisanobu Adachi; Yoshihide Kawasaki; Masafumi Kikuchi; Akihiro Ito; Nariyasu Mano (Frontiers Media S.A., 2020)
Pazopanib is an orally available multi-tyrosine kinase inhibitor and has been used to treat renal cell carcinoma (RCC). Here, we report the case of a patient with RCC with an increased prothrombin time-international normalized ratio (PT-INR) due to pazopanib therapy. In addition, we have reported the change in the blood levels of pazopanib. A 75-year-old man underwent a left nephrectomy for RCC. Four years later, his cancer recurred and pazopanib therapy was initiated. He was also taking warfarin for atrial fibrillation and his PT-INR was constant at approximately 2. His warfarin dose was reduced from 3.5 mg/day to 3.0 mg/day on day 10 because his PT-INR increased from 2.19 to 3.07 compared to that before starting pazopanib. On day 28, his PT-INR further increased to 4.34, and his aspartate aminotransferase, alanine transaminase, and alkaline phosphatase levels increased. The target concentration of pazopanib was 20.5 to 50.3 µg/mL, but his blood concentrations were 92.1 µg/mL on day 6 and 93.7 µg/mL on day 13. Therefore, both pazopanib and warfarin were discontinued. One week later, his laboratory tests recovered, and hence, warfarin treatment was resumed. However, pazopanib therapy was terminated due to concerns about liver dysfunction. His hepatic dysfunction and increased PT-INR were considered to be due to pazopanib treatment. Pazopanib has been reported to have no effect on the pharmacokinetics of warfarin in clinical patients. In this case, blood levels of pazopanib were abnormally high, possibly causing liver dysfunction and drug interactions, leading to his PT-INR prolongation. TDM monitoring, in addition to the recommended monitoring for pazopanib hepatotoxicity, may help identify patients at risk for drug interactions. For patients receiving concomitant pazopanib and warfarin, close monitoring of PT-INR is warranted.